Evaluating management options to reduce Lake Erie algal blooms using an ensemble of watershed models. (15th February 2021) - Martin, Jay F.; Kalcic, Margaret M.; Aloysius, Noel; Apostel, Anna M.; Brooker, Michael R.; Evenson, Grey; Kast, Jeffrey B.; Kujawa, Haley; Murumkar, Asmita; Becker, Richard; Boles, Chelsie; Confesor, Remegio; et al.
Abstract: Reducing harmful algal blooms in Lake Erie, situated between the United States and Canada, requires implementing best management practices to decrease nutrient loading from upstream sources. Bi-national water quality targets have been set for total and dissolved phosphorus loads, with the ultimate goal of reaching these targets in 9-out-of-10 years. Row crop agriculture dominates the land use in the Western Lake Erie Basin thus requiring efforts to mitigate nutrient loads from agricultural systems. To determine the types and extent of agricultural management practices needed to reach the water quality goals, we used five independently developed Soil and Water Assessment Tool models to evaluate the effects of 18 management scenarios over a 10-year period on nutrient export. Guidance from a stakeholder group was provided throughout the project, and resulted in improved data, development of realistic scenarios, and expanded outreach. Subsurface placement of phosphorus fertilizers, cover crops, riparian buffers, and wetlands were among the most effective management options. But, only in one realistic scenario did a majority (3/5) of the models predict that the total phosphorus loading target would be met in 9-out-of-10 years. Further, the dissolved phosphorus loading target was predicted to meet the 9-out-of-10-year goal by only one model and only in three scenarios. In all scenarios evaluated, the 9-out-of-10-year goal was not met based on the average of model predictions. Ensemble modeling revealed general agreement about the effects of several practices although some scenarios resulted in a wide range of uncertainty. Overall, our results demonstrate that there are multiple pathways to approach the established water quality goals, but greater adoption rates of practices than those tested here will likely be needed to attain the management targets. Graphical abstract: Image 1 Highlights: Multiple models showed variability in meeting water quality goals. There was agreement among models that some practices can reduce phosphorus loads. Reducing dissolved reactive phosphorus is more difficult than total phosphorus. Reaching water quality goals requires substantial adoption of conservation practices. Stakeholder guidance improved scenario development, interpretation, and outreach.